Non-decarbonylative photochemical versus thermal activation of Bu4N[Fe(CO)3(NO)] – the Fe-catalyzed Cloke–Wilson rearrangement of vinyl and arylcyclopropanes. Issue 12 (16th September 2015) - Lin, Che-Hung; Pursley, Dominik; Klein, Johannes E. M. N.; Teske, Johannes; Allen, Jennifer A.; Rami, Fabian; Köhn, Andreas; Plietker, Bernd
Abstract : TBA[Fe] catalyzes the rearrangement of vinyl and arylcyclopropanes under thermal or photochemical conditions. Abstract : The base metal complex Bu4 N[Fe(CO)3 (NO)] (TBA[Fe]) catalyzes the rearrangement of vinyl and arylcyclopropanes both under thermal or photochemical conditions to give the corresponding vinyl or aryldihydrofurans in good to excellent yields. Under photochemical conditions the reaction is performed at room temperature. Spectroscopic investigations show that the metal carbonyl catalyst is not decarbonylated. The best performance was observed at a wavelength of 415 nm. icMRCI+Q analysis of the excited singlet and triplet states of the [Fe(CO)3 (NO)] anion was performed and used to calculate the vertical excitation energies which are in good agreement with the experimental data. CASSCF analysis indicates that the Fe center in all excited states of the ferrate becomes more electrophilic while adopting a distorted tetrahedral configuration. Both aspects have a positive synergistic effect on the formation of the initial π-complex with the incoming organic substrate.